Analysis of the Energy Consumption Structure in Shanxi Province Based on Carbon Emissions - Li, Jinjian; Zhang, Yan; Liu, Gengyuan; Zheng, Hongmei; Xia, Linlin; Sun, Xiaoxi (Journal of Environmental Accounting and Management, 2026)
As one of the most important energy supply and consumption provinces in China, Shanxi has been under great pressure in carbon abatement because of its high-carbon economy. Thus, it is imperative to adjust the energy structure and explore effective ways for energy conservation and carbon emission reduction in Shanxi Province. Based on the energy consumption and carbon emission of different types of energy source, this paper analyzed the carbon emission of each industrial sector in Shanxi from 2003 to 2012, discussed the transfer of carbon emission responsibility caused by inter-provincial energy import and export, and introduced an energy consumption structure index to evaluate the structural characteristics of energy consumption for specific sectors. The results revealed that, during 2003 to 2012, the carbon emission in Shanxi Province increased significantly, which was mainly contributed by the consumption of coal and coke; while the carbon emission of briquette and natural gas grew fastest. From the sectoral perspective, industry and thermal power sectors contributed most to the total carbon emission of this province. About 20%-30% of the electricity produced by the thermal power sector was used for the external supply, so from the perspective of regional fair, the regions who receive the energy should take some responsibility for the corresponding carbon emission. The overall energy structure of Shanxi Province improved gradually. Except for the continuous low emission efficiency of thermal power and heating sectors, most of other sectors showed the energy structure trend towards higher emission efficiency, which represented a lower carbon-intensive development. Based on the energy structure characteristics, recommendations covering both energy conservation and emission reduction were provided to support the lowcarbon economy development in Shanxi Province. Three major measures included the industrial restructuring, energy structure adjustment, and emission reduction on transportation.